2019
DOI: 10.1111/hex.12980
|View full text |Cite
|
Sign up to set email alerts
|

‘The Future is Probably Now’: Understanding of illness, uncertainty and end‐of‐life discussions in older adults with heart failure and family caregivers

Abstract: Background Earlier end‐of‐life communication is critical for people with heart failure given the uncertainty and high‐risk of mortality in illness. Despite this, end‐of‐life communication is uncommon in heart failure. Left unaddressed, lack of end‐of‐life discussions can lead to discordant care at the end of life. Objective This study explores patients' and caregivers’ understanding of illness, experiences of uncertainty, and perceptions of end‐of‐life discussions in advanced illness. Design Interpretive descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Although four challenges are discussed independently, these challenges are intertwined with one another. The challenges are identified in the context of participants’ understanding of illness, which is reported in a separate article [29]. Briefly, participants had detailed knowledge of heart failure management and its self-care behaviors, and yet, participants appeared limited in their understanding of the consequences of illness and its progressive nature.…”
Section: Resultsmentioning
confidence: 99%
“…Although four challenges are discussed independently, these challenges are intertwined with one another. The challenges are identified in the context of participants’ understanding of illness, which is reported in a separate article [29]. Briefly, participants had detailed knowledge of heart failure management and its self-care behaviors, and yet, participants appeared limited in their understanding of the consequences of illness and its progressive nature.…”
Section: Resultsmentioning
confidence: 99%
“…They saw recurrent hospitalizations as normal, without recognition of the progressive nature of the disease and threat of mortality. 16 Not-confronting language is also important for HCPs, who reported a need for support in initiation of palliative care needs conversations. A survey found that half of the clinicians taking care of patients with CHF reported reasons not to discuss palliative care, such as their own discomfort, the feeling that patient or family were not ready, or fear of destroying hope.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced HF presents an unpredictable course that some healthcare professionals may feel insecure treating [ 5 ]. Moreover, patients may have a falsely optimistic perception about the progression of the disease and delay end- of-life discussions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%